Adsorption Behavior of Methylene Blue Dye by Novel CrossLinked O-CM-Chitosan Hydrogel in Aqueous Solution: Kinetics, Isotherm and Thermodynamics - Nouf Faisal Alharby (MDPI AG, 2021)
The chemical cross-linking of carboxymethyl chitosan (O-CM-chitosan), as a method for its modification, was performed using trimellitic anhydride isothiocyanate to obtain novel cross-linked O-CM-chitosan hydrogel. Its structure was proven using FTIR, XRD and SEM. Its adsorption capacity for the removal of Methylene Blue (MB) dye from aqueous solution was studied. The effects of different factors on the adsorption process, such as the pH, temperature and concentration of the dye, in addition to applications of the kinetic studies of the adsorption process, adsorption isotherm and thermodynamic parameters, were studied. It was found that the amount of adsorbed MB dye increases with increasing temperature. A significant increase was obtained in the adsorption capacities and removal percentage of MB dye with increasing pH values. An increase in the initial dye concentration increases the adsorption capacities, and decreases the removal percentage. It was found that the pseudo-second-order mechanism is predominant, and the overall rate of the dye adsorption process appears to be controlled by more than one step. The Langmuir model showed high applicability for the adsorption of MB dye onto O-CM-chitosan hydrogel. The value of the activation energy (Ea) is 27.15 kJ mol−1 and the thermodynamic parameters were evaluated. The regeneration and reuse of the investigated adsorbent was investigated.